Associations Between Stress and Cardiovascular Disease Risk Factors Among Million Hearts Priority Populations. Issue 7 (September 2019) - Gawlik, Kate Sustersic; Melnyk, Bernadette Mazurek; Tan, Alai
Purpose: To estimate the effects of stress on hypertension and high cholesterol with a focus on Million Hearts priority populations. Design: A population-based cross-sectional survey on cardiovascular health and its risk factors. Setting: Million Hearts cardiovascular community screenings Sample: Deidentified data were collected on a convenience sample of 59 798 participants. Measures: Self-reported stress score using the Perceived Stress Scale-4 (PSS-4), blood pressure, and total cholesterol. Analysis: Descriptive statistics were used to estimate the prevalence of high stress (PSS-4 score ≥ 9), prehypertension or hypertension, and elevated total cholesterol. Multiple logistic regression modeling was used to estimate the effect of stress on the risk of elevated blood pressure and total cholesterol. Results: Twenty-four percent of the participants had high stress. Younger participants had an increased prevalence of high stress than older participants (28% vs 20%, P < .001). African Americans had a high prevalence of stress (26.4%), prehypertension or hypertension (65.4%), and elevated total cholesterol (48.6%). Compared to those with low stress, high stress was associated with significant higher risks of having prehypertension/hypertension (odds ratio [OR] = 1.40, 95% confidence interval [CI] = 1.28-1.53) and elevated cholesterol (OR = 1.53, 95% CI = 1.41-1.66). Conclusions: Stress needs to be routinely identified and treated, especially in Million Hearts priority populations. More research is needed in designing culturally sensitive and effectively tailored interventions relative to both stress and disease management.